Expression of the SNAI2 transcriptional repressor is regulated by C16-ceramide. Issue 6 (3rd June 2019) - Lu, Ping; White-Gilbertson, Shai; Nganga, Rose; Kester, Mark; Voelkel-Johnson, Christina
ABSTRACT: Ceramide synthase 6 (CerS6) is an enzyme that preferentially generates pro-apoptotic C16 -ceramide in the sphingolipid metabolic pathway. Reduced expression of CerS6 has been associated with apoptosis resistance and recent studies point to a role for CerS6 in epithelial mesenchymal transition (EMT). Because cells that undergo EMT are also more resistant to apoptosis, we hypothesized that reduced expression of CerS6 could induce changes that are associated with EMT. We found that shRNA-mediated knockdown of CerS6 increases expression of the EMT transcription factor SNAI2 but not SNAI1 or TWIST. Treatment with C6 -ceramide nanoliposomes (CNL) resulted in a preferential increase in C16 -ceramide and suppressed SNAI2 transcriptional activation and protein expression. The increase in C16 -ceramide following CNL treatment was dependent on CerS activity and occurred even when CerS6 shRNA was expressed. shRNA against CerS5, which like CerS6 preferentially generates C16 -ceramide, also decreased transcriptional activation of SNAI2, suggesting a role for C16 -ceramide rather than a specific enzyme in the regulation of this transcription factor. While loss of CerS6 has been associated with apoptosis resistance, we found that cells lacking this protein are more susceptible to the effects CNL. In summary, our study identifies SNAI2 as a novel target whose expression can be influenced by C16 -ceramide levels. The potential of CNL to suppress SNAI2 expression has important clinical implications, since elevated expression of this transcription factor has been associated with an aggressive phenotype or poor outcomes in several types of solid tumors.